Legal Analysis of Fraud and Embezzlement in Banking Credit Practices: A Case Study of Sukmaji in Cianjur Regency - Nia Rohani; Anas Lutfi (Publikasi Indonesia, 2026)
This research examines the juridical aspects of criminal acts of fraud and embezzlement in banking credit practices that occurred to Mr. Sukmaji, a retired BUMN employee, perpetrated by PT Samida, which acted as a broker and partner of Bank Capital. This study aims to analyze the validity of credit agreements, the elements of criminal acts, and the legal responsibility of the financial institutions involved, based on the Civil Code, Criminal Code, and Banking Law. It also aims to provide input to banking regulators and consumer protection agencies to improve supervisory mechanisms in banking partnerships with third parties. The results of the study indicate that there are elements of negligence in supervision by banking institutions toward their intermediary partners, as well as abuse of trust by third parties, which causes losses to the debtor. Credit agreements made through intermediaries or partners are not legally valid because they do not meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code, due to defects in the elements of consent and authority. The actions of the agents constitute fraud (Article 378) and embezzlement (Article 372). Therefore, banks are legally responsible for protecting consumers under Consumer Protection and Banking Laws. This study recommends strengthening third-party supervision, enhancing financial literacy for retirees, implementing the know-your-agent principle, and increasing OJK oversight and law enforcement